PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR DI MADRASAH IBTIDAIYAH SAMBINA’E KOTA BIMA - Indriani, Irma (FASHLUNA, 2022)
This study aims to determine the use of the surrounding environment as a learning resource. The approach used in this research is descriptive qualitative. Data collection is done by interview technique. The interview technique was to interview the principal, two teachers and one student. Furthermore, all data is processed by the stages of qualitative data analysis, namely data reduction, data model (data display), conclusion drawing/verification. The results of the study indicate that the utilization of the environment has not been carried out optimally because there are no adequate facilities and infrastructure to support the use of the environment as a learning resource.